Estudo Químico de Croton muscicarpa Müll. Arg. (Euphorbiaceae) - Freitas, Joao Vito Barroso de (2012)
This work describes the chemical composition of Croton muscicarpa (Euphorbiacea), a native plant to Northeastern Brazil, popularly known as “velame-de-cheiro”. The species was collected in the Chapada Diamantina, Bahia, and its phytochemical investigation was carried out through the isolation and characterization of secondary metabolites present in the ethanol extract from stems and hexane extract from roots. The sesquiterpenes, spathulenol and 6α-methoxy-cyperene, this latter is reported for the first time in the literature, were isolated from the stems. From roots, the triterpene, acetyl aleuritolic acid (AAA) and the polimethoxyflavone, 5-hydroxy-3,6,7,3',4'-pentamethoxyflavone (artemetin) were isolated. The isolation of chemical constituents was performed by conventional chromatographic methods and structural determination of the isolated substances accomplished through the use of spectrometric techniques such as Infrared (IR), Mass Spectrometry (MS) and Nuclear Magnetic Resonance Hydrogen (1H NMR) and Carbon-13 (13C NMR), including two-dimensional techniques (COSY,HSQC, HMBC and NOESY) and comparison with the data described in the literature.